Behavioural and emotional problems, intellectual impairment and health-related quality of life in patients with organic acidurias and urea cycle disorders - Jamiolkowski, Dagmar; Kölker, Stefan; Glahn, Esther M; Barić, Ivo; Zeman, Jiri; Baumgartner, Matthias R; Mühlhausen, Chris; Garcia-Cazorla, Angels; Gleich, Florian; Haege, Gisela; Burgard, Peter; E-IMD consortium (Journal of inherited metabolic disease, 2016)
BACKGROUND: Organic acidurias (OADs) and urea cycle disorders (UCDs) are inborn metabolic disorders with a risk for acute and chronic metabolic decompensation resulting in impairments of the central nervous system and other organ systems. So far, there is no systematic study of intellectual functioning, behavioural/emotional problems and health-related quality of life (HRQoL), and how these domains are connected. METHODS: Data of 152 patients with OADs (n = 100) and UCDs (n = 52) from the European Registry and Network of intoxication type Metabolic Diseases (E-IMD) using standardized instruments were compared with normative data. RESULTS: Behavioural/emotional problems are increased in OADs or UCDs patients by a factor of 2.5 (3.0), in female asymptomatic carriers of X-linked inherited UCD ornithine transcarbamylase deficiency (fasOTCD) by a factor of 1.5. All groups show similar patterns of behavioural/emotional problems, not different from epidemiological data. Mental disability (IQ ≤ 70) was found in 31% of OAD, 43% of UCD, but not in fasOTCD subjects. HRQoL was decreased in the physical domain, but in the normal range. Behavioural/emotional problems were significantly associated with intellectual functioning (OR = 6.24, 95%CI: 1.39-27.99), but HRQoL was independent from both variables. CONCLUSIONS: Patients with OADs and UCDs show increased frequencies of mental disability and behavioural/emotional problems. Profiles of behavioural/emotional problems were similar to epidemiological data. Intellectual disability and behavioural/emotional problems were strongly associated. Patients' HRQoL was in the normal range, possibly compensated by coping strategies of their families. Diagnostics and clinical care of OAD/UCD patients should be improved regarding behavioural/emotional, intellectual and quality of life aspects.
Keywords: Ornithine Carbamoyltransferase Deficiency Disease; Intellectual Disability; mužské pohlaví; vrozené poruchy cyklu močoviny; mentální retardace; kvalita života; Child, Preschool; Mental Disorders; ženské pohlaví; Urea Cycle Disorders, Inborn; Humans; předškolní dítě; vrozené poruchy metabolismu; metabolické nemoci; emoce; Metabolism, Inborn Errors; Metabolic Diseases; duševní poruchy; Emotions; Female; Quality of Life; nemoc z nedostatku ornithinkarbamoyltransferázy; lidé; Male